Формування галузевої структури сільськогосподарських підприємств України - Яворська, Тетяна Іванівна; Яворская, Татьяна Ивановна; Yavorska, Tetiana (My University, 2019)
UK: В роботі розглянуто стан галузевої структури сільськогосподарських підприємств України, в тому числі малих фермерських господарств в 2014-2018 роках. Встановлено, що тенденція зменшення частки тваринницької продукції в загальному обсязі реалізації продукції зберігається. Виявлені відмінності зміни галузевих структур в основних природно-кліматичних зонах України. Розглянуто вплив галузевої структури на рівень рентабельності виробництва продукції. EN: Abstract. Formulation of the problem. A study of the industry structure of enterprises showed that the efficiency of production depends largely on the composition of the industries and the relationship between them. Ignoring the problem of sectoral restructuring of the production leads structure to negative consequences. Therefore, managing a rational combination of industries in agricultural enterprises has been and remains an urgent problem. Research results. The main factors influencing the development of agriculture are: climatic conditions, specialization and concentration of production, market conditions, scientific and technological progress and economic policy of the state. The changes in the branch structure of agricultural enterprises and small farms of Ukraine are analyzed for the period 2014-2018. Sectoral structure was determined by the indicator (income) from the sale of agricultural products. It is determined that the share of crop production in total sales continues to increase. Accordingly, the share of livestock products is decreasing. This has a certain impact on the level of profitability of production of enterprises, especially small farms. The differences in the sectoral structures of agricultural production in the three major natural and climatic zones of Ukraine are revealed. It is determined that the most significant changes occurred in the sectoral structure of agricultural enterprises of the Steppe. Conclusions. The modern sectoral structure of Ukrainian agricultural enterprises is far from rational. The study showed that the downward trend in the share of livestock products in total agricultural production persists. In small farmers, this reduction is accelerating, especially in the steppe zone. Sectoral structure influences production efficiency. Its change in dynamics causes a change in the level of profitability of production. In order to increase the efficiency of their activities, agricultural enterprises must constantly improve their sectoral structure of production. This, in turn, will change the economic parameters of their development.
Formation of the sectoral structure of agricultural enterprises of Ukraine
Keywords: галузева структура; сільськогосподарські підприємства; фермерські господарства; рослинництво; тваринництво; рівень рентабельності; branch structure; agricultural enterprise; crop production; animal husbandry; level of profitability